The Role of Government Policy Onmanagement State-Owned Enterprises in Increasing State Income (Study at PT Kawasan Berikat Nusantara Persero) - Sattar Taba; Tjahya Supriatna; Ermaya Suradinata; Mansyur Achmad (Budapest International Research and Critics University, 2022)
The problems that entangle State-Owned Enterprises in fulfilling their obligations as mandated by Law Number 19 of 2003 concerning State-Owned Enterprises which also apply to all provisions stipulated in Law Number 40 of 2007 concerning Limited Liability Companies are; the weak implementation of the digitalization system in the management of State-Owned Enterprises, so that there are still constraints on efficiency and increasing company productivity, as well as the ability of HR-State-Owned Enterprises to innovate in maintaining the existence of State-Owned Enterprises as a support for state revenue. The research method is a mindset, which is well prepared to conduct research and to achieve research objectives. Research itself is a scientific work that must be carried out in a systematic, orderly, orderly manner, both regarding the procedure and in thinking about the material. Research can be defined as an effort to find, develop and test the truth of a knowledge that is carried out through scientific methods. Therefore, in carrying out research, one must pay attention to scientific principles which consist of collecting data, classifying, analyzing, and also interpreting the facts and connecting them with empirical reality to test their truth. Based on the description above, using qualitative research through a descriptive approach, the researcher can see the problems that exist in the field, then describe the phenomena and analyze the relationships that occur between related phenomena and are contained in the background of the problem, the formulation of the problem. , and also the focus of this research. The results show that the collaborative process of the public sector often reflects implicitly its relationship to the hierarchy of actors. Governments (or public services) are externally often a burden on collaborative structures, especially the public sector. This is a fact especially in state-owned companies. In accordance with the results of observations made during the research process, it was also found that the bureaucracy, in fact, can be a (secret) power in accessing information directly to the Minister of State-Owned Enterprises (Government) who based on the law is declared as the owner of the company.